Optimizing Service Quality and Promotions for Ride-Hailing User Loyalty - Astri Romandang Banjarnahor; M.Syaifal Anuggrah Illahi; Mhd Ahli Akbar (Jurnal Ilmu Multidisiplin, 2025)
This study analyzes the influence of price, promotion, and service quality on customer satisfaction and loyalty in ride-hailing services in Malaysia. Using the Structural Equation Modeling (SEM) method, data from 332 respondents were analyzed to understand the dynamics between these variables. The results of the study show that price and service quality significantly affect customer satisfaction, while promotion plays a greater role in improving the perception of service quality which ultimately has an impact on customer loyalty. Service quality is identified as a key factor that determines customer satisfaction and loyalty. The research highlights the importance of competitive pricing strategies, effective promotions, and improved service quality to retain customers in an increasingly competitive ride-hailing market. These findings provide practical guidance for ride-hailing companies in designing strategies to increase customer satisfaction and loyalty.